2002
DOI: 10.1086/343738
|View full text |Cite
|
Sign up to set email alerts
|

Valacyclovir in the Treatment of Facial Herpes Simplex Virus Infection

Abstract: The objective of this multicenter, randomized, double-blind, noninferiority trial was to investigate valacyclovir as treatment for facial herpes simplex virus (HSV) outbreaks. In total, 308 otherwise healthy outpatients self-initiated therapy with valacyclovir, either 1000 mg twice daily for 1 day or 500 mg twice daily for 3 days, for treatment of one facial HSV episode. Aborted lesions were the primary end point. Secondary end points included episode and pain resolution and lesion healing. By regimen (1 or 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…They found that more than half of their patients achieved an aborted or partially-aborted lesion after treatment with either of two regimens: 500mg twice daily for three days or 1g twice daily for one day. 13 The study also showed a significant reduction in time to episode and pain resolution when compared with earlier data. They concluded that further work was needed to determine the best dose and duration for this treatment.…”
Section: Herpes Simplex Infectionsupporting
confidence: 58%
“…They found that more than half of their patients achieved an aborted or partially-aborted lesion after treatment with either of two regimens: 500mg twice daily for three days or 1g twice daily for one day. 13 The study also showed a significant reduction in time to episode and pain resolution when compared with earlier data. They concluded that further work was needed to determine the best dose and duration for this treatment.…”
Section: Herpes Simplex Infectionsupporting
confidence: 58%
“…36 Compared with topical agents, oral antivirals allow systemic drug exposure, faster access to the sites of viral replication, greater bioavailability, less frequent dosing, and improved patient compliance. 36,77,[229][230][231] Oral antivirals also provide a practical and appropriate route for long-term suppressive therapy in patients with frequent, severe outbreaks of herpes infection. 16,36 In addition, intervention with systemic antivirals is indicated for eczema herpeticum, neonatal herpes, HSV encephalitis, ocular herpes, and HSV infections in the immunocompromised patient.…”
Section: Managementmentioning
confidence: 99%
“…53,259 The purpose is to abort lesions, to minimize clinical manifestations, and to reduce infectivity during attacks rather than the number of outbreaks. 3,230,259,262 As episodic therapy depends on the presence of prodrome, patients must be vigilant in the recognition of early signs and symptoms and timely initiation of therapy at the prodrome or within 1 day of the outbreak. 36,56,124,259,267 In a recent study of HSL in adults, oral intake of 2 g of valcyclovir twice a day for 1 day, started during the prodrome, aborted some lesions and reduced the duration of an outbreak by 1 day.…”
Section: Treatment Of Recurrent Herpetic Infectionsmentioning
confidence: 99%
“…21 One multicenter, randomized, double-blind, noninferiority trial focused on dose and duration of valacyclovir in recurrent herpes labialis. 15 The study included 308 patients who self-treated with 1000 mg twice daily for one day (n = 154) or 500 mg twice daily (n = 154) for 3 days. Eligible subjects were ≥12 years old who experienced ≥4 episodes per year with a positive viral culture.…”
Section: Valacyclovirmentioning
confidence: 99%